Urgensi Kerja Sama Sektor Pariwisata untuk Meningkatkan Hubungan Thailand-Kamboja Pasca Sengketa Kuil Preah Vihear - Marshanda Fitria Intan (LP4MK STKIP PGRI Lubuklinggau, 2022)
The Urgency of Tourism Sector Cooperation to Improve Thailand Cambodia Relations After the Dispute on the Preah Vihear Temple. This study aims to determine the urgency of cooperation in the tourism sector to improve relations between Thailand and Cambodia after the conflict dispute. Tracing data was carried out using literature study. The results show that the disputed conflict between Thailand and Cambodia which has made relations between the two countries worse has been resolved through the ASEAN mechanism in a peaceful manner. After the dispute was resolved, the two parties sought cooperation in the tourism sector to improve relations between the two, such as the implementation of a single visa and D3 tourism student exchange. So that cooperation in the tourism sector has an important role in restoring the relationship between the two.